Large flow shears around auroral beads at substorm onset. Issue 19 (1st October 2013) - Hosokawa, K.; Milan, S. E.; Lester, M.; Kadokura, A.; Sato, N.; Bjornsson, G.
<x xml:space="preserve">Abstract</x> [1] We present a fine‐scale electrodynamic structure behind the auroral beads observed immediately before substorm onset, as inferred from high spatial and temporal resolution measurements of substorm with an all‐sky TV camera (ATV) and a coherent high frequency radar of Super Dual Auroral Radar Network in Iceland. On the night of 24 September 2006, the ATV observed eastward propagating auroral beads in the initial brightening arc of a substorm just prior to the poleward expansion. During the sequential passage of the beads across the radar beams, the radar detected large velocity flow shears whose magnitude was in excess of 0.27 s−1. The observations suggest that flow shears were located very close to the center of the beads; thus, they corresponded to electric fields converging toward the beads, which is consistent with the existence of upward field‐aligned currents (FACs) flowing out of the beads. The temporal and spatial resolutions of the current radar measurement were still insufficient for fully resolving the detailed electrodynamic structure behind the fast moving auroral beads. At least, however, we can suggest the existence of highly localized filamentary FAC structures behind the beads, which would be an important consequence of possible plasma instabilities operating in the M‐I coupling region or near the equatorial plane of the magnetosphere.